ADAPTASI AGRI-FOOD SUPPLY CHAIN FRAMEWORK DALAM PENGUKURAN KINERJA RANTAI PASOK HORTIKULTURA SUB-SEKTOR BUAH PISANG - , AZIYZUL A ABDI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Agricultural-products supply chain requires different management than non-agri-products supply chain. Lumajang is one of banana Mas production centers which product output have been able to meet the needs of local market and in part to the market outside of the city. The problem faced is the conceptual supply chain management that applied in Lumajang had not evaluated yet. The banana Mas supply chain in Lumajang, like other fruit-products supply chain, doesnât has a performance refference according to the characteristics of agricultural products so that the supply chain performance could not be monitored and improved yet. The aims of this study was to obtain performance indicators which could be a performance measurement refference and gain an overview of the supply chain performance over the years. Agri-food Supply Chain framework is one of the agricultural product supply chain measurement system which includes four performance categories namely: efficiency, flexibility, responsiveness, and quality with a range of performance indicators in it. This research was carried out by adjusting agri-food supply chain framework with banana Mas supply chains characteristic. Respondents were selected consisting of farmers, farmer groups, distributors, and wholesaler/retail. The study begins with an analysis of indicators importance scores based on respondent perceptions and conditions of the existing supply chain. Then, performance measurement performed using the indicators that have been selected based on the indicator importance scores with a scale of 5. Nineteen indicators were resulted for banana supply chain performance measurement are divided into four main categories. Highest importance scores obtained from indicator of profit (4.60) for efficiency